Cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs and preparation method of cobalt-nickel catalyst

The cobalt nickel catalyst prepared by the solvothermal method solves the problems of low-temperature catalytic degradation of VOCs in the prior art with low temperature catalytic degradation and insufficient sulfur resistance, and achieves efficient propane degradation and good sulfur resistance.

CN119680547AActive Publication Date: 2025-03-25ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411802360.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing single-component transition metal oxide catalysts are difficult to effectively catalyze the degradation of VOCs, especially propane at low temperatures, and there are problems of high catalytic temperatures and insufficient sulfur resistance.

Method used

A composite catalyst was prepared by solvothermal method. Co(NO3)3·6H2O and Ni(NO3)3·6H2O were dissolved in ethylene glycol in a certain proportion, and cetyl trimethylammonium bromide and urea were added, and cobalt nickel catalyst with excellent catalytic properties was prepared by autoclave treatment and calcination.

Benefits of technology

The propane degradation rate of 90% at 195°C was achieved, and the propane degradation was achieved at 200°C. The catalyst had a low catalytic temperature and good sulfur resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680547A_ABST
    Figure CN119680547A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs (volatile organic compounds) and a preparation method of the cobalt-nickel catalyst. Co (NO3) 3.6 H2O and Ni (NO3) 3.6 H2O are dissolved in ethylene glycol according to the substance amount greater than 5: 1, hexadecyl trimethyl ammonium bromide is added under continuous stirring, and stirring is performed to form a solution; then urea is introduced into the solution, after stirring is finished, the mixture is transferred into a stainless steel high-pressure kettle with a polytetrafluoroethylene lining, and the high-pressure kettle is placed in a drying oven to be kept for several hours; cooling to room temperature, centrifuging the precipitate, washing and drying; and heating and calcining in an air atmosphere to obtain the cobalt-nickel catalyst. The catalyst prepared through the method is stable in performance, the propane degradation rate can reach 90% at the temperature of 195 DEG C, and propane can be completely degraded at the temperature of 200 DEG C; and the catalyst has certain stability and anti-poisoning performance in a sulfur-containing environment. The preparation method is simple and suitable for batch preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a cobalt-nickel catalyst for catalytic degradation of VOCs at low temperature and a preparation method thereof. Background Art

[0002] VOCs are important precursors to PM2.5 and ozone in the atmosphere, causing significant harm to human health and the environment. Propane is a VOC with a stable CC bond and CH bond structure, which is difficult to be completely oxidized at low temperatures. Therefore, its catalytic degradation has become an important issue in the field of environmental protection. In order to reduce VOCs emissions and achieve environmentally friendly production, it is particularly important to develop efficient catalysts for the low-temperature catalytic degradation of propane.

[0003] Single-component transition metal oxide catalysts have limited effects on the catalytic degradation of VOCs. The synergistic effect between different metal components in the composite catalyst helps to enhance electron mobility, improve the redox ability of the catalyst and the generation rate of active oxygen species, thereby significantly improving the low-temperature catalytic degradation efficiency of VOCs. Therefore, it is very necessary to further explore a composite catalyst for the degradation of VOCs at low temperatures. Summary of the invention

[0004] In order to solve at least one of the above problems, the present invention provides a cobalt-nickel catalyst for catalytic degradation of VOCs at low temperature and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical means: The first aspect of the present invention provides a method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs, comprising the following steps: (1) Dissolve Co(NO3)3·6H2O and Ni(NO3)3·6H2O in ethylene glycol at a ratio of (1-9):1, add hexadecyltrimethylammonium bromide under constant stirring, and stir to form a pink homogeneous solution; (2) Introduce urea into the solution, seal it and continue stirring for several hours; (3) After stirring, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and the autoclave was placed in an oven for several hours; (4) The autoclave was cooled to room temperature, the resulting precipitate was centrifuged, and the precipitate was washed alternately with ethanol and deionized water and dried; (5) The dried precipitate is calcined in an air atmosphere according to a heating program to obtain a cobalt-nickel catalyst.

[0006] In some embodiments of the present invention, in step (2), the molar ratio of urea / (Co+Ni) is 1.50.

[0007] In some embodiments of the present invention, in step (3), the temperature in the oven is 180-200° C. and the holding time is 10-12 h.

[0008] In some embodiments of the present invention, in step (4), the temperature of the drying step is 80-90° C. and the drying time is 10-12 hours.

[0009] In some embodiments of the present invention, in step (5), the heating rate of the temperature raising program is (4-6)°C / min.

[0010] In some embodiments of the present invention, in step (5), the calcination temperature is 250-350° C. and the calcination time is 4-6 hours.

[0011] The second aspect of the present invention provides a cobalt-nickel catalyst prepared by the method described in the first aspect.

[0012] The third aspect of the present invention provides the use of the cobalt-nickel catalyst described in the second aspect in the low-temperature catalytic degradation of VOCs.

[0013] In some embodiments of the present invention, the VOCs are short-chain alkanes such as propane and ethane.

[0014] In some embodiments of the present invention, the temperature is between 180° C. and 230° C. In some embodiments of the present invention, the catalytic degradation temperature of propane is below 200° C.

[0015] Beneficial effects of the present invention Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs prepared by a solvothermal method. The catalyst prepared by the solvothermal method has stable performance and can achieve a 90% propane degradation rate at 195°C and complete propane degradation at 200°C. The preparation method is simple and suitable for batch preparation. At the same time, the composite catalyst is made of Co and Ni in a certain ratio. When the ratio of Co:Ni is greater than 5:1, it can meet the T of propane catalytic degradation. 90 All are below 200°C, and when the Co:Ni ratio is 9:1, the catalytic temperature is the lowest, which is 195°C. Compared with the existing disclosed propane catalysts, it has a lower catalytic temperature, and the catalyst has certain sulfur resistance, and has certain stability and anti-poisoning performance in a sulfur-containing environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The catalytic effects of the catalysts prepared in Examples 1-3 of the present invention on propane are compared; Figure 2The figure shows the comparison of the catalytic effects of the catalysts prepared in Examples 1, 4-7 of the present invention on propane; Figure 3 The catalytic effects of the catalysts prepared in Examples 8-10 of the present invention and Comparative Examples 1-2 on propane are compared; Figure 4 The catalytic effects of the catalysts prepared in Examples 10-12 of the present invention on propane are compared; Figure 5 The catalytic effects of catalysts prepared by different preparation methods on propane are compared; Figure 6 The SEM morphology comparison diagrams of catalysts prepared by different preparation methods are shown; among them, (a) is Co9Ni1_P, (b) is Co9Ni1_R, and (c) is Co9Ni1_S; Figure 7 The surface element composition analysis diagram of the Co9Ni1_P catalyst prepared in Example 10 is shown; Figure 8 The results of the sulfur resistance test of the Co9Ni1_P catalyst prepared in Example 10 at T = 250°C are shown; Fig. 9 The results of the sulfur resistance test of the Co9Ni1_P catalyst prepared in Example 10 at T=300°C are shown; Fig.10 The catalytic degradation effect of Co9Ni1 catalyst on propane at different gas hourly space velocities is shown; Fig.11 The comparison of the catalytic effects of the catalysts repeatedly prepared by the method of the present invention on propane is shown; Fig.12 The catalytic effect of Co9Ni1 catalyst on ethane and propane is shown. DETAILED DESCRIPTION

[0017] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.

[0019] The technical solution of the present application is further described in detail below in conjunction with specific implementation methods.

[0020] Example 1 Preparation of Mn5Ce1 Catalyst The preparation process is as follows: Dissolve 12.5 mmol of Mn(NO3)2·H2O and 2.5 mmol of Ce(NO3)3·6H2O in 30 mL of deionized water; mix 20 mmol of NaOH and 5 mmol of anhydrous Na2CO3 and dissolve them in 30 mL of deionized water; then alternately introduce the two solutions into 25 mL of deionized water, and control the solution pH = 10±0.5; after the titration is completed, centrifuge the precipitate, wash and dry; and calcine at a high temperature in an air atmosphere to obtain the Mn5Ce1 catalyst.

[0021] Example 2 Preparation of Co5Mn1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 12.5 mmol of Co(NO3)3·6H2O and 2.5 mmol of Mn(NO3)2·H2O.

[0022] Example 3 Preparation of Co5Ni1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 12.5 mmol of Co(NO3)3·6H2O and 2.5 mmol of Ni(NO3)3·6H2O.

[0023] The catalysts obtained by compounding the different transition metals in Examples 1 to 3 were prepared at C3H8=2,000ppm and WHSV=30,000 h -1 Under the reaction conditions, the catalytic degradation effects of the three were compared. The results are as follows Figure 1 shown.

[0024] The results show that the Mn5Ce1 catalyst with Mn as the main active phase can achieve complete degradation of propane at above 300°C, and its catalytic activity is significantly lower than that of the Co5Mn1 and Co5Ni1 catalysts with Co as the main active phase. It is preliminarily determined that the composite system with Co as the main active phase has a more superior catalytic oxidation activity for propane.

[0025] Example 4 Preparation of Mn2Ce1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 10 mmol of Mn(NO3)2·H2O and 5 mmol of Ce(NO3)3·6H2O.

[0026] Example 5 Preparation of Mn1Ce1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 7.5 mmol of Mn(NO3)2·H2O and 7.5 mmol of Ce(NO3)3·6H2O.

[0027] Example 6 Preparation of Mn1Ce2 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 5 mmol of Mn(NO3)2·H2O and 10 mmol of Ce(NO3)3·6H2O.

[0028] Example 7 Preparation of Mn1Ce5 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 2.5 mmol of Mn(NO3)2·H2O and 12.5 mmol of Ce(NO3)3·6H2O.

[0029] The degradation effects of the Mn-Ce catalysts prepared with different Mn-Ce composite ratios in Examples 1, 4 to 7 on propane were compared. The results are as follows: Figure 2 shown.

[0030] The results show that the degradation effects of Mn-Ce catalysts with different ratios on propane are ranked as follows: Mn1Ce1>Mn2Ce1>Mn5Ce1>Mn1Ce2>Mn1Ce5. Although adjusting the composite ratio helps to improve the catalytic activity of Mn-Ce, the most superior Mn1Ce1 still requires a reaction temperature of 275°C to achieve complete degradation of propane. The low-temperature activity is still significantly different from that of Co-based catalysts and still has certain limitations.

[0031] Example 8 Preparation of Co1Ni1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 7.5 mmol of Co(NO3)3·6H2O and 7.5 mmol of Ni(NO3)3·6H2O.

[0032] Example 9 Preparation of Co5Ni1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 12.5 mmol of Co(NO3)3·6H2O and 2.5 mmol of Ni(NO3)3·6H2O.

[0033] Example 10 Preparation of Co9Ni1 Catalyst The preparation process is the same as that of Example 1, except that the components in the metal salt solution are 13.5 mmol of Co(NO3)3·6H2O and 1.5 mmol of Ni(NO3)3·6H2O.

[0034] Comparative Example 1 Preparation of Co3O4 Catalyst The preparation process is the same as that of Example 1, except that the component in the metal salt solution is 15 mmol Co(NO3)3·6H2O.

[0035] Comparative Example 2 Preparation of NiO2 Catalyst The preparation process is the same as that of Example 1, except that the component in the metal salt solution is 15 mmol Ni(NO3)3·6H2O.

[0036] The Co-Ni catalysts prepared by using different Co-Ni composite ratios in Examples 8 to 10 and the catalysts prepared in Comparative Examples 1 and 2 were compared for the degradation effect on propane. The results are as follows: Figure 3 shown.

[0037] The results show that the composite catalyst with Co as the main active phase has excellent catalytic oxidation activity for propane. When the Co:Ni ratio is greater than 5:1, the T 90 All are below 200°C, and when the Co:Ni ratio is 9:1, the catalytic temperature is the lowest, which is 195°C.

[0038] In Examples 1 to 10, the co-precipitation method was used to prepare the catalyst. During the exploration process, it was found that the co-precipitation method was affected by factors such as unstable solution pH and fluctuations in titration rate, which would cause catalyst particle agglomeration and affect uniformity, and there was a certain fluctuation in the activity of catalysts in different batches.

[0039] To this end, we explored different preparation methods.

[0040] Example 11 Preparation of Co9Ni1 Catalyst by Hydrothermal Method The preparation process is as follows: 13.5 mmol of Co(NO3)3·6H2O and 1.5 mmol of Ni(NO3)3·6H2O were dissolved in 60 mL of deionized water and stirred to form a solution; then 30 mmol of urea was introduced into the solution. After stirring, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and the autoclave was placed in an oven at 180°C for 12 hours; cooled to room temperature, the precipitate was centrifuged, washed and dried; and calcined at a high temperature in an air atmosphere to obtain the Co9Ni1 catalyst prepared by the hydrothermal method.

[0041] Example 12 Preparation of Co9Ni1 Catalyst by Solvothermal Method The preparation process is as follows: 13.5 mmol of Co(NO3)3·6H2O and 1.5 mmol of Ni(NO3)3·6H2O were dissolved in 60 mL of ethylene glycol, and 15 mmol of hexadecyltrimethylammonium bromide was added under constant stirring to form a solution; then 22.5 mmol of urea was introduced into the solution. After stirring, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and the autoclave was placed in an oven at 180°C for 12 hours; cooled to room temperature, the precipitate was centrifuged, washed and dried; and calcined in an air atmosphere to obtain the Co9Ni1 catalyst prepared by the solvothermal method.

[0042] The catalytic degradation effects of Co9Ni1 catalysts prepared by coprecipitation, hydrothermal and solvothermal methods in Examples 10 to 12 were compared for propane. Figure 4 shown.

[0043] The results showed that compared with the hydrothermal method and the coprecipitation method, the Co9Ni1 catalyst prepared by the solvothermal method with hexadecyltrimethylammonium bromide as an additive showed better catalytic performance at low temperature: at 2,000 ppm propane and a mass space velocity of 30,000 mL g -1 h -1 , under 195℃ conditions, a propane degradation rate of 90% can be achieved, and at 200℃, propane can be completely degraded.

[0044] Example 13 Co9Ni1 catalyst morphology control The preparation process is the same as that of Example 12. During the preparation process, ammonia water and oleylamine were used instead of hexadecyltrimethylammonium bromide (CTAB) to assist in constructing a reducing solution atmosphere, and Co9Ni1_R and Co9Ni1_S catalysts were prepared. The catalyst prepared by adding hexadecyltrimethylammonium bromide (CTAB) in Example 12 was named Co9Ni1_P.

[0045] (1) The Co9Ni1 catalyst prepared above was used to compare the catalytic degradation of propane. The results are as follows: Figure 5 shown.

[0046] The results show that among the three catalysts, the Co9Ni1_P catalyst exhibits the best effect in the catalytic degradation of propane alone, and the Co9Ni1_R and Co9Ni1_S catalysts also exhibit excellent low-temperature activity, further verifying the superior performance of the active component formula in the propane degradation reaction. The degradation effects of the three catalysts under the condition of a single propane component are slightly different, and all can achieve complete conversion of propane at about 200°C.

[0047] (2) The surface structure of the Co9Ni1 catalyst prepared above was observed using a field emission scanning electron microscope (SEM) of the German ZEISS Gemini SEM 360. The morphology comparison diagram is shown in FIG. Figure 6 As shown, (a) is the SEM characterization results of Co9Ni1_P, (b) is Co9Ni1_R, and (c) is Co9Ni1_S.

[0048] The results show that the Co9Ni1_P catalyst prepared by solvothermal method using CTAB as an additive presents a granular morphology with a high specific surface area, which can provide more active sites, and may be the reason for its relatively high catalytic activity. By adding different additives, catalysts with different morphologies can be prepared: Co9Ni1_R with nanorod structure and Co9Ni1_S with porous sheet structure.

[0049] (3) The elemental composition of the catalyst surface was analyzed using a field emission electron microscope from the German ZEISS Gemini SEM 360. Figure 7 shown.

[0050] The results showed that the Co and Ni elements of Co9Ni1_P were evenly distributed and the O content was rich, which indicated that the solvothermal method could achieve good dispersion of different elements and optimize the synergistic effect between different components.

[0051] (4) In addition to the original reaction gas, 50 ppm of SO2 was introduced to simulate the actual industrial sulfur-containing atmosphere. The sulfur resistance of the Co9Ni1_P catalyst was evaluated at temperatures of T = 250 °C and T = 300 °C. The results are shown in Figure 2. Figure 8 and Fig. 9 shown.

[0052] The results show that at 250°C, the Co9Ni1_P catalyst rapidly deactivated in an atmosphere containing 50 ppm SO2; while at 300°C, the catalyst maintained a 100% propane conversion rate within 10 hours and a conversion efficiency of >90% within 16 hours. This shows that the Co9Ni1_P composite catalyst has certain stability and anti-poisoning performance in a sulfur-containing environment.

[0053] (5) At a gas hourly space velocity of 30,000 h -1 、60,000mL h -1 、90,000mL h -1 The catalytic degradation effect of Co9Ni1_P catalyst on propane was tested under the following conditions. Fig.10 shown.

[0054] The results show that the Co9Ni1 catalyst has a high -1 Under the condition of propane catalytic degradation, T 90 Below 195°C, at around 200°C, complete degradation can be achieved.

[0055] (6) The Co9Ni1_P catalyst was re-prepared using the method of Example 15 and tested for propane catalytic degradation. The results are as follows: Fig.11 shown.

[0056] The results showed that the performance of catalysts prepared by the solvothermal method from different batches was basically consistent, showing good repeatability.

[0057] (7) The catalytic degradation effect of ethane was tested using Co9Ni1_P catalyst. The results are as follows: Fig.12 shown.

[0058] The results show that the Co9Ni1_P catalyst can also achieve low-temperature catalysis of ethane. 90 At around 225°C, complete degradation can be achieved at around 250°C.

[0059] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.

Claims

1. A method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs, characterized in that: The steps include: (1) Dissolve Co(NO3)3·6H2O and Ni(NO3)3·6H2O in ethylene glycol at a ratio of greater than 5:1, add an equal amount of hexadecyltrimethylammonium bromide under constant stirring, and stir to form a pink homogeneous solution; (2) Introduce urea into the solution, seal it and continue stirring for several hours; (3) After stirring, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and the autoclave was placed in an oven for several hours; (4) The autoclave was cooled to room temperature, the resulting precipitate was centrifuged, and the precipitate was washed alternately with ethanol and deionized water and dried; (5) The dried precipitate is calcined in an air atmosphere according to a heating program to obtain a cobalt-nickel catalyst.

2. The method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs according to claim 1, characterized in that: In the step (2), the molar ratio of urea / (Co+Ni) is 1.

50.

3. The method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs according to claim 1, characterized in that: In the step (3), the temperature in the oven is 180-200° C. and maintained for 10-12 hours.

4. The method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs according to claim 1, characterized in that: In the step (4), the temperature of the drying step is 80-90°C and the drying time is 10-12h.

5. The method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs according to claim 1, characterized in that: In the step (5), the heating rate of the heating program is (4-6)°C / min.

6. The method for preparing a cobalt-nickel catalyst for low-temperature catalytic degradation of VOCs according to claim 1, characterized in that: In the step (5), the calcination temperature is 250-350° C. and the calcination time is 4-6 hours.

7. A cobalt-nickel catalyst prepared by the method according to any one of claims 1 to 6.

8. Use of the cobalt-nickel catalyst as claimed in claim 7 in low-temperature catalytic degradation of VOCs.

9. The use according to claim 8, characterized in that: The VOCs are short-chain alkanes propane and ethane.

10. The use according to claim 8, characterized in that: The temperature is between 180°C and 230°C.

Citation Information

Patent Citations

  • Catalyst slurry, VOCs catalytic oxidation catalyst, and preparation methods and applications of catalyst slurry and VOCs catalytic oxidation catalyst

    CN118874486A

  • Cobalt-cerium catalyst for catalyzing low-carbon alkane at low temperature as well as preparation method and application of cobalt-cerium catalyst

    CN119034752A

  • Supported Catalyst, Its Activated Form, and their Preparation and Use

    US20150231612A1

  • Shaped catalysts and processes

    US4895994A